Allelopathic Effects of Winter Legumes on Germination and Seedling Indicators of Various Summer Cereals - Ayub Muhammad; Ijaz Muhammad Kashif; Tariq Muhammad; Tahir Muhammad; Nadeem Muhammad Ather (Agricultura Tropica et Subtropica, 2012)
In the present study, the putative allelopathic potential of aqueous extracts (10 % w/v) of three legumes, i.e. alfalfa, berseem and brassica spp., including distilled water treatments as check were evaluated on germination and early seedling growth indicators of rice, sorghum and millet under laboratory conditions. The treatments were compared in completely randomized design with factorial arrangements in four replications. The recorded observations clearly indicated that the germination process and seedling growth of receptor plants were negatively affected in the presence of legume extracts. The extract of Brassica had the strongtest inhibitory effect on germination process in form of increased mean germination time (MGT) and lowered the coefficient of velocity of germination (CVG), germination % age and germination index (GI) as compared to other extracts. Likewise, the lowest root and shoot length, their fresh and dry weight was also noted in petri dishes with Brassica extracts. Among the receptor crops, rice was the most susceptible in term of both seedling growth and germination attributes. The interaction between test crops and legume extracts was found to be significant for most of studied parameters except germination % age, fresh and dry weight of root and shoot. The presence of allelochemicals in the studied legumes entitled them to be used in weed management programme and is also signal for designing specific production technologies able to reduce their effects on succeeding crops.